Strategies and Challenges in Teacher Development: A Comparative Multisite Study in Indonesian Higher Education - Topan Iskandar; Mesiono Mesiono; Masganti Sit (AL-ISHLAH: Jurnal Pendidikan, 2025)
Lecturer quality is a key determinant of higher education performance, yet universities face persistent challenges in developing teaching staff effectively. This study examines and compares strategies for lecturer development and the obstacles encountered by Indonesian universities in improving academic staff quality. Using a qualitative approach with a multisite study design, the research was conducted at four universities—two public and two private—selected to reflect geographical diversity and institutional characteristics. Data were collected through in-depth interviews, participant observation, and analysis of institutional documents, and were analyzed thematically. The findings indicate that lecturer development strategies commonly include continuous professional training, scholarship programs for advanced study, international collaboration, and performance-based incentive systems. Despite these efforts, implementation is constrained by limited budgets, resistance to organizational change, complex administrative procedures, and unequal access to resources across institutions. The study highlights the need for more adaptive and context-sensitive lecturer development policies. Strengthening inter-institutional collaboration and aligning development programs with institutional capacities and local needs are critical to overcoming existing barriers. This study contributes practical insights for policymakers and university leaders in designing more effective and sustainable lecturer development strategies tailored to diverse institutional contexts.